2019
DOI: 10.1121/1.5111870
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in hearing: Probing the role of estrogen signaling

Abstract: Hearing loss is the most common form of sensory impairment in humans, with an anticipated rise in incidence as the result of recreational noise exposures. Hearing loss is also the second most common health issue afflicting military veterans. Currently, there are no approved therapeutics to treat sensorineural hearing loss in humans. While hearing loss affects both men and women, sexual dimorphism is documented with respect to peripheral and central auditory physiology, as well as susceptibility to age-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 78 publications
4
55
0
Order By: Relevance
“…Previous studies have shown that males experience more effects after exposure to occupational noise than females [ 1 , 66 ]. This may be due to males usually having greater exposure to noise at work than females due to differences in occupational categories, economic sectors of employment, and lifetime work history.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that males experience more effects after exposure to occupational noise than females [ 1 , 66 ]. This may be due to males usually having greater exposure to noise at work than females due to differences in occupational categories, economic sectors of employment, and lifetime work history.…”
Section: Resultsmentioning
confidence: 99%
“…Another possible reason is the hormone-driven physiological differences between sexes. Several animal and human studies have demonstrated that women may be protected against hearing loss because of estrogen and its signaling pathways [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the species/strain differences (and ignoring effects of the observable inter-laboratory differences in immunostaining signal-to-noise), other sources of difference in synaptic recovery include sex 44 and age-at-exposure 4 . Here we studied primarily females, but saw no significant sex differences at 1 month post exposure (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Given this neuroprotective role, it is perhaps unsurprising that there is a wealth of literature that estrogen, the classical estrogen receptors (ERs), and the estrogen-related receptors (ERRs) play a critical role in maintaining auditory function (Charitidi, Meltser, Meltser, Tahera, & Canlon, 2009;Delhez, Lefebvre, Lefebvre, Pequeux, Malgrange, & Delacroix, 2020;Hultcrantz, Simonoska, Simonoska, & Stenberg, 2006;Shuster, Depireux, Depireux, Mong, & Hertzano, 2019;Williamson, Zhu, Zhu, Pineros, Ding, & Frisina, 2020). Despite this, our understanding of the modes of action of estrogen in the cochlea are far from clear.…”
Section: Estrogen-far More Than a Sex Hormonementioning
confidence: 99%